2005
DOI: 10.1002/neu.20117
|View full text |Cite
|
Sign up to set email alerts
|

Ciliary neurotrophic factor protects retinal ganglion cells from axotomy-induced apoptosis via modulation of retinal gliain vivo

Abstract: Adenoviral-mediated transfer of ciliary neurotrophic factor (CNTF) to the retina rescued retinal ganglion cells (RGCs) from axotomy-induced apoptosis, presumably via activation of the high affinity CNTF receptor alpha (CNTFRalpha) expressed on RGCs. CNTF can also activate astrocytes, via its low affinity leukemia inhibitory receptor beta expressed on mature astrocytes, suggesting that CNTF may also protect injured neurons indirectly by modulating glia. Adenoviral-mediated overexpression of CNTF in normal and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(40 citation statements)
references
References 82 publications
2
38
0
Order By: Relevance
“…Part of these phenotypic changes has been reported previously at shorter time periods using injections of recombinant CNTF (see Introduction) and adenovirusmediated gene transfer of CNTF in the rat striatum (Lisovoski et al, 1997) and retina (van Adel et al, 2005). In addition, the changes in the phenotype of astrocytes were reproduced in our in vitro model of primary striatal neuron/astrocyte cultures, demonstrating that whatever the delivery system used, extracellular Figure 6.…”
Section: Discussionsupporting
confidence: 69%
“…Part of these phenotypic changes has been reported previously at shorter time periods using injections of recombinant CNTF (see Introduction) and adenovirusmediated gene transfer of CNTF in the rat striatum (Lisovoski et al, 1997) and retina (van Adel et al, 2005). In addition, the changes in the phenotype of astrocytes were reproduced in our in vitro model of primary striatal neuron/astrocyte cultures, demonstrating that whatever the delivery system used, extracellular Figure 6.…”
Section: Discussionsupporting
confidence: 69%
“…Beyond that, many studies have shown that exogenous CNTF and LIF have significant protective effects on injured ganglion cells and photoreceptors (see e.g. Cayouette et al, 1998;Mey and Thanos, 1993;M€ uller et al, 2009;Ueki et al, 2008;van Adel et al, 2005). Thus, upregulation of CNTF and LIF in activated M€ uller cells may in turn strongly influence neuronal responses to injury.…”
Section: Discussionmentioning
confidence: 95%
“…164 Optic nerve transection also induced a time dependent loss of RGC, approximately 50% of RGC were lost 1 week after the insult, and 80% to 100% of RGC disappeared 2 weeks after optic nerve transaction. 159,[164][165][166][167][168][169][170][171][172][173][174][175] The death of RGC is mediated by apoptosis, which can be reduced by inhibition of apoptosis mediators. [176][177][178] A corresponding time-dependent disappearance of Thy-1 and NF-L mRNA was observed.…”
Section: Optic Nerve Injurymentioning
confidence: 99%